2012
DOI: 10.1074/jbc.m112.375840
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol Transfer Protein, Cytoplasmic 1 (PITPNC1) Binds and Transfers Phosphatidic Acid

Abstract: Background: Phosphatidylinositol transfer protein, cytoplasmic 1 (PITPNC1) (alternative name, RdgB␤) promotes metastatic colonization and angiogenesis in humans. Results: We demonstrate that RdgB␤ is a phosphatidic acid (PA)-and phosphatidylinositol-binding protein and binds PA derived from the phospholipase D pathway. Conclusion: RdgB␤ is the first lipid-binding protein identified that can bind and transfer PA. Significance: PA bound to RdgB␤ is a likely effector downstream of phospholipase D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 44 publications
5
83
0
1
Order By: Relevance
“…Although Nir2 has been shown to transfer PI between membranes in vitro (9), in vivo evidence supporting inter-organelle lipid transfer mediated by Nir2 or other PITPs is missing. In this study, we devise approaches to selectively manipulate PIP 2 precursors at the ER and Golgi, and we demonstrate that Nir2-mediated PM PIP 2 replenishment is dependent on PI at the ER membrane.…”
Section: Phosphatidylinositol (Pi)mentioning
confidence: 99%
“…Although Nir2 has been shown to transfer PI between membranes in vitro (9), in vivo evidence supporting inter-organelle lipid transfer mediated by Nir2 or other PITPs is missing. In this study, we devise approaches to selectively manipulate PIP 2 precursors at the ER and Golgi, and we demonstrate that Nir2-mediated PM PIP 2 replenishment is dependent on PI at the ER membrane.…”
Section: Phosphatidylinositol (Pi)mentioning
confidence: 99%
“…Biochemical analysis has shown that the PITP domain of class II PITPs have distinct lipid binding and transfer activities from those of the class I PITPs. Whereas class I PITPs are PI/phosphatidylcholine (PC) transfer proteins, the class II PITP domains have distinct properties [28,29]. In a recent study the PITP domain of RDGBα has been shown to bind and transfer both PI and phosphatidic acid (PA) but not PC in vitro [24].…”
Section: Proposed Functions Of the Sub-microvillar Cisternaementioning
confidence: 98%
“…family, bound either PtdIns or phosphatidic acid (PA) [35]). Recent studies indicate that human Nir2 (PITPNM1) and Drosophila RdgBα, which are multidomain homologues of RdgBβ, function at ER-PM contact sites, transferring PtdIns and PA in opposite directions [36,37].…”
Section: Heterotypic Lipid Exchange Between Organelles: a General Mecmentioning
confidence: 99%
“…Using a class II PITP domain [35], Nir2 would mediate PtdIns/PA exchange to promote PtdIns synthesis and the replenishment of the PM PtdIns(4,5)P2 pool, thereby maintaining the signalling competence of the cell. For clarity, E-Syt1 is represented as a monomer.…”
Section: Heterotypic Lipid Exchange Between Organelles: a General Mecmentioning
confidence: 99%